Legitimation capacity: System-level resources and political skills in public policy. Issue 3 (1st September 2015) - Woo, J J; Ramesh, M; Howlett, M
Abstract: This paper conceptualizes political competences at the system level of capabilities to function as "legitimation capacity" in a policy context. It identifies trust in the political, social, economic, and security spheres as the key element driving this capacity. Trust ensures that state actions and institutions are perceived as legitimate and receive public support, which in turn allows political skills to be exercised, preventing political or institutional decay and policy ineffectiveness. Conceptualization of legitimation capacity as comprising trust across political, social, economic, and security dimensions offers a useful framework for analyzing and estimating a government's capacity in different policy spheres. It provides a practical tool for estimating any deficiencies in legitimation capacity that a government may face. While governments may be endowed with different levels of legitimate capacity when they first attain office, they may over time work on building up capacity by focusing on the spheres in which they may be lacking. Conversely, they may lose legitimacy if their efforts in these areas are counter-productive.